Implementation Of Central Aceh Regency Government Policy In Ecotourism Development - Maulana, Jefrie; Eza Aulia; Dara Quthni Effida; Ilka Sandela (Jurnal Hukum Samudra Keadilan, 2024)
The Aceh Tengah Regency ecotourism development policy is based on the Qanun RIPPARDA since 2018-2025. On its way, the development of ecotourism over the past five years has not had a significant impact. The formulation of the problem in this study is how the implementation of the Aceh Tengah regency government policy in the development of ecotourism and what are the obstacles faced by the Aceh Tengah regency government in implementing the policy. The aim in this this research are to find out and explain the implementation of the policy of the Central Aceh district government in the development of ecotourism and provide an overview of the obstacles experienced by the Central Aceh district government in implementing policies on ecotourism development. This research is a qualitative research by applying descriptive analysis method and empirical juridical approach. The results showed that the ecotourism development policy in Central Aceh Regency has not been supported by separate implementing regulations such as regulations within the scope of tourism destinations, tourism industry, marketing and tourism institutions based on the provisions of tourism legislation. Constraints faced in policy implementation include, among others, a regulatory vacuum that has an impact on the emergence of illegal businesses, the non-absorption of local revenue in the field of tourism to the maximum, and the emergence of ecotourism businesses that do not rely on environmental protection, the high cost of licensing administration in the field of environmental impact control and the behaviour of people who are not friendly to tourists